Network Pharmacologic Analysis of Dendrobium officinale Extract Inhibiting the Proliferation of Gastric Cancer Cells - Wei, Lianping; Dong, Wenhao; Han, Zhen; Chen, Chen; Jin, Qing; He, Jinling; Cai, Yongping (Frontiers in Pharmacology, 2022)
Gastric cancer (GC) is one of the three most lethal cancers worldwide. Dendrobium officinale (D. officinale) is a traditional Chinese medicine (TCM), and its extract can significantly inhibit the proliferation of gastric cancer cells. However, there is no unified conclusion on its potential active components and possible mechanism. This paper aims to explore the potential active components, targets and cell pathways of D. officinale extracts in inhibiting the proliferation of gastric cancer cells by using network pharmacology and cytology experiments. In this paper, UPLC-MS/MS was used to identify the main chemical components in the extraction of D. officinale, and ADME model was used to screen potential active components. The network pharmacology methods such as target prediction, pathway identification and network construction were used to determine the inhibitory mode of D. officinale extract on gastric cancer cell proliferation. MTT, fluorescence confocal, clone formation and flow cytometry were used to verify the inhibitory activity of D. officinale extract on gastric cancer cell proliferation in vitro. The results showed that 178 chemical components were identified from D. officinale extract by UPLC-MS/MS. Network pharmacology analysis showed that 13 chemical components had the potential to inhibit the proliferation of gastric cancer cells, involving 119 targets and 20 potential signaling pathways. In vitro experiments confirmed that D. officinale extract could significantly inhibit the proliferation of gastric cancer cells. Therefore, we believe that D. officinale extract can inhibit the proliferation of gastric cancer cells through multi-component, multi-target and multi-pathway.